Ladies on the Lot: Women, Car Sales, and the Pursuit of the American Dream - Lawson, Helene M. (Rowman & Littlefield Publishers, 2000)
In this unique and lively ethnography of women who sell cars, sociologist Helene M. Lawson and the “ladies on the lot” take readers behind the scenes of one of the last bastions of a predominantly male workplace: the car dealership. Linking the women’s own stories within the broader framework of gender and occupation, Lawson presents an engaging and important case study on the impact of gender differences and behavior in the workplace. In doing so, Ladies on the Lot makes an original contribution to the field and will be of interest for a wide variety of courses, including gender and occupations, the sociology of work, the sociology of women, and various courses in women’s studies and qualitative methods.